1993
DOI: 10.1128/aem.59.1.285-289.1993
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of dibenzofuran, fluorene, and dibenzo-p-dioxin by Staphylococcus auriculans DBF63

Abstract: Staphylococcus auriculans DBF63, which can grow on dibenzofuran (DBF) or fluorene (FN) as the sole source of carbon and energy, was isolated. Salicylic acid and gentisic acid accumulated in the culture broth of this strain when DBF was supplied as a growth substrate. Also, the formation of 9-fluorenol, 9-fluorenone, 4-hydroxy-9-fluorenone, and 1-hydroxy-9-fluorenone was demonstrated, and accumulation of 1,la-dihydroxy-1-hydro-9-fluorenone was observed when this strain grew on FN. On the basis of these results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(46 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…However, the other degradation products in this study have not previously been identified as metabolites of P. ostreatus. Both 4-hydroxy-9fluorenone and 4-hydroxyperinaphthenone have been identified as dead-end products during bacterial degradation of fluorene [34] and pyrene [31], respectively. On the other hand, 4oxapyrene-5-one has previously been identified in diesel exhaust [30], where it probably was a product of chemical/ photochemical oxidation of pyrene.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other degradation products in this study have not previously been identified as metabolites of P. ostreatus. Both 4-hydroxy-9fluorenone and 4-hydroxyperinaphthenone have been identified as dead-end products during bacterial degradation of fluorene [34] and pyrene [31], respectively. On the other hand, 4oxapyrene-5-one has previously been identified in diesel exhaust [30], where it probably was a product of chemical/ photochemical oxidation of pyrene.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial reductive dechlorination of polychlorinated dibenzo-p-dioxins and dibenzofurans (CDD/Fs) in sediments is an important environmental process, because it has the potential of decreasing the toxicity of CDD/Fs if lateral chlorines are removed (Ballerstedt et al, 1997;Vargas et al, 2001;Gruden et al, 2003;Fennell et al, 2004;Ahn et al, 2005Ahn et al, , 2007Yoshida et al, 2005;Liu & Fennell, 2008). Dechlorination may also be advantageous because lesser chlorinated congeners of CDD/ Fs are more susceptible to subsequent aerobic degradation (Fortnagel et al, 1990;Strubel et al, 1991;Happe et al, 1993;Monna et al, 1993;Wittich, 1998). Dechlorination of CDD/Fs is a slow process with a time frame of months or years.…”
Section: Introductionmentioning
confidence: 99%
“…The great environmental concern of PAHs is due to their toxic, mutagenic, and carcinogenic properties (Monna et al, 1993). The use of analytical chemistry techniques as the only tool in the evaluation of risk of contaminated soils should be questioned and the presence of complex mixtures of xenobiotics and natural compounds should be considered.…”
Section: Introductionmentioning
confidence: 99%